2023
DOI: 10.1371/journal.ppat.1011097
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a HIV-1 IN-Allosteric inhibitor complex at 2.93 Å resolution: Routes to inhibitor optimization

Abstract: HIV integrase (IN) inserts viral DNA into the host genome and is the target of the strand transfer inhibitors (STIs), a class of small molecules currently in clinical use. Another potent class of antivirals is the allosteric inhibitors of integrase, or ALLINIs. ALLINIs promote IN aggregation by stabilizing an interaction between the catalytic core domain (CCD) and carboxy-terminal domain (CTD) that undermines viral particle formation in late replication. Ongoing challenges with inhibitor potency, toxicity, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 122 publications
3
8
0
Order By: Relevance
“…This engagement is anti-parallel, which differs from the original dimeric CTD solution NMR structure (PDB 1IHV) 47 , but resembles recently described crystallographic packing interactions within IN assemblies containing bound ALLINI (PDB 8CTA) 48 ( Figure 2c , bottom right). Notably, the fact that the anti-parallel CTD:CTD interface is now observed within the IN tetramer indicates that this interaction mode is biologically relevant, which could not be concluded from packing assemblies observed crystallographically 48 . Such diverse contacts contributed by CTDs help stabilize and maintain the tetrameric conformation and add to our understanding of the promiscuity of the CTD, which additionally engages with other protein domains and/or nucleic acids in the intasome 8 .…”
Section: Resultssupporting
confidence: 47%
See 2 more Smart Citations
“…This engagement is anti-parallel, which differs from the original dimeric CTD solution NMR structure (PDB 1IHV) 47 , but resembles recently described crystallographic packing interactions within IN assemblies containing bound ALLINI (PDB 8CTA) 48 ( Figure 2c , bottom right). Notably, the fact that the anti-parallel CTD:CTD interface is now observed within the IN tetramer indicates that this interaction mode is biologically relevant, which could not be concluded from packing assemblies observed crystallographically 48 . Such diverse contacts contributed by CTDs help stabilize and maintain the tetrameric conformation and add to our understanding of the promiscuity of the CTD, which additionally engages with other protein domains and/or nucleic acids in the intasome 8 .…”
Section: Resultssupporting
confidence: 47%
“…Lastly, the CTDs engage one another at the twofold axis through hydrophobic contacts ( Figure 2c , bottom left). This engagement is anti-parallel, which differs from the original dimeric CTD solution NMR structure (PDB 1IHV) 47 , but resembles recently described crystallographic packing interactions within IN assemblies containing bound ALLINI (PDB 8CTA) 48 ( Figure 2c , bottom right). Notably, the fact that the anti-parallel CTD:CTD interface is now observed within the IN tetramer indicates that this interaction mode is biologically relevant, which could not be concluded from packing assemblies observed crystallographically 48 .…”
Section: Resultssupporting
confidence: 47%
See 1 more Smart Citation
“…In their mode of binding to HIV-1 IN, INLAIs mimic the LEDGF/p75 integrase binding domain (IBD), which engages the same pocket on the CCD dimer interface ( 38 ). Recent X-ray crystallography and biochemical studies revealed that INLAIs act as molecular glues, promoting formation of a pathological interface involving the HIV-1 CCD dimer and a C-terminal domain (CTD) ( 39 42 ). While HIV-1 IN forms stable tetramers ( 24 , 43 , 44 ) under physiological conditions, the formation of the additional, drug-induced IN-IN interface leads to uncontrolled multimerization of the viral protein.…”
Section: Introductionmentioning
confidence: 99%
“…Upon binding to the V-shaped cavity at the CCD dimer interface, ALLINIs act as molecular glues to recruit CTD (31)(32)(33). Therefore, we tested how Y99H/A128T IN mutations affected formation of the CCD-PIR-CTD complex.…”
Section: Biochemical Mechanisms Of the Iny99h/a128t Resistance To Pirmentioning
confidence: 99%